The Effect of Organizational Commitment, Leadership and Culture Toward Performance of ASN Employees in The Regional Secretariat of Kaltim District - Gaibu, Ilyas (Lembaga Penelitian dan Pengabdian kepada Masyarkat-Universitas Terbuka, 2022)
This study aims to examine the effect of independent variables which include organizational commitment, leadership style, and organizational culture toward dependent variable, namely employee performance. Research data is primary data in the form of a questionnaire with a Likert scale distributed directly to all research respondents. The sample in this study were employees of the State Civil Apparatus (ASN) within the scope of the Regional Secretariat of East Halmahera Regency with a total of 105 respondents. The data analysis method in this study uses multiple linear regression analysis.The results obtained by the regression equation . The partial analysis results obtained t test, organizational commitment of leadership style of (6,1434), organizational culture of table then is rejected. So it can be concluded that there is a partial effect on employee performance. While the results of the simultaneous analysis using the F test obtained the calculated F value (69,032) > F table then s rejected. Thus, it can be concluded that organizational commitment, leadership style, and organizational culture together (F test) has a positive effect on the performance of ASN employees in the Regional Secretariat of East Halmahera district.